Power system fundamentals - Ponce, Pedro; Molina, Arturo; Mata, Omar; Ibarra, Luis; MacCleery, Brian (Taylor & Francis, CRC Press, 2018)
"Smart grids are linked with smart homes and smart meters. These smart grids are the new topology for generating, distributing, and consuming energy. If these smart devices are not connected in a smart grid, then they cannot work properly; hence, the conventional power systems are swiftly changing in order to improve the quality of electrical energy. This book covers the fundamentals of power systems, which are the pillars for smart grids, with a focus on defining the smart grid with theoretical and experimental electrical concepts. It begins by covering electric circuits, which are the basic systems in smart grids, and finishes with a complete smart grid concept. The book allows the reader to build a foundation of understanding with basic and advanced exercises that run on simulation before moving to experimental results. It is intended for readers who want to comprehensively cover both the basic and advanced concepts of smart grids. The book includes Matlab-Simulink examples and experimental results."--Provided by publisher.